Integrating AI-Enhanced Industrial IoT Ecosystems with FIWARE for Smart Cities: A Scalable Enterprise Solution - Medeiros Jr., Valério G. de; de Araújo, Daniel Sabino A.; Lopes, Frederico; Martins, Rodrigo S.; Medeiros, Welkson R. de; do Nascimento, Leonardo S.; Lopes Neto, Alfredo F.; Rodrigues, Erich M.; da Silva, Jorge P.; da Silva, Felipe A. C. M.; Souto, Moisés C. de B. (Anais do Workshop de Computação Urbana (CoUrb); 2025: Anais do IX Workshop de Computação Urbana, 2025)
This study explores how the FIWARE and SAMANAU1 platforms can be integrated to strengthen IoT ecosystems in smart cities and industrial applications. The proposed architecture leverages open standards, machine learning, and cloud, fog, and edge computing to enable solutions such as smart city dashboards, public infrastructure monitoring, and environmental sensor networks. The key benefits include greater scalability, interoperability, and real-time decision-making capabilities. Comparative analyses demonstrate that open-source approaches offer advantages over proprietary systems by reducing costs and fostering innovation. This work highlights the importance of FIWARE in advancing commercial IoT solutions for more sustainable urban and industrial development.